2010
DOI: 10.1007/s12671-010-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ruminative Thinking Mediate the Clinical Benefits of Mindfulness: Preliminary Findings

Abstract: We investigated whether the clinical benefits of mindfulness training are mediated by a reduction in maladaptive rumination and an increase in adaptive rumination. Participants in eight-session mindfulness training were assessed before and after treatment, while waiting-list controls were assessed at similar times. For the mindfulness training, a treatment manual was derived from the mindfulness-based cognitive therapy procedure and adapted to account for the consequences of stress, anxiety, and depression rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 27 publications
8
62
0
7
Order By: Relevance
“…Overall, the findings of this study are consistent with theoretical predictions regarding the mechanisms through which mindfulness-based interventions treat depression, one of which is that mindfulness training alleviates symptoms of depression through reducing maladaptive rumination (Teasdale et al 1995;Heeren and Philippot 2011;Shahar et al 2010). The present study further highlighted the role of shifts in metacognitive beliefs about rumination as an additional mechanism of change underlying the effects of mindfulness training.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the findings of this study are consistent with theoretical predictions regarding the mechanisms through which mindfulness-based interventions treat depression, one of which is that mindfulness training alleviates symptoms of depression through reducing maladaptive rumination (Teasdale et al 1995;Heeren and Philippot 2011;Shahar et al 2010). The present study further highlighted the role of shifts in metacognitive beliefs about rumination as an additional mechanism of change underlying the effects of mindfulness training.…”
Section: Discussionsupporting
confidence: 84%
“…However, contrary to previous evidence suggesting that scores. This may be because most of this evidence is based on training in state mindfulness rather than trait mindfulness differences (e.g., Deyo et al 2009;Heeren and Philippot 2011;Kingston et al 2007). Although Borders et al (2010) reported an association with trait mindfulness, they measured mindfulness with the Mindfulness Attention Awareness Scale (Brown and Ryan 2003) and this scale has more in common with measures of attentional cognitive failures than with other measures of trait mindfulness (Cheyne, Carriere and Smilek 2006;Grossman 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have demonstrated beneficial effects of mindfulness on outcomes such as pain management (Kabat-Zinn et al 1985;Rosenzweig et al 2010;Zautra et al 2008), immune function (Creswell et al 2009;Davidson et al 2003;Fang et al 2010), changes in brain areas associated with emotion (Davidson et al 2003;Hölzel et al 2010;Hölzel et al 2011), ruminative thoughts (Deyo et al 2009;Heeren & Philippot 2011;Jain et al 2007;Labelle et al 2010;Shapiro et al 2007), cognitive distortions ), positive reappraisal coping (Garland et al 2011), preventing relapse of depression (Kuyken et al 2008;Teasdale et al 2000), anxiety and negative affect VĂžllestad et al 2011), perceived stress and selfcompassion (Shapiro et al 2005), and hope ). Meta-analyses of mindfulness-based stress reduction programs suggest that these interventions are promising for individuals coping with a variety of physical and mental health issues including pain, cancer, heart disease, depression, anxiety, and stress in healthy people (Bohlmeijer et al 2010;Chiesa & Serretti 2009;Grossman et al 2004;Hofmann et al 2010).…”
Section: Introductionmentioning
confidence: 99%